2022
DOI: 10.2174/1573399818666211130142153
|View full text |Cite
|
Sign up to set email alerts
|

Type I Diabetes Mellitus and Insulin Therapy on Bone Microarchitecture, Composition and Mechanical Properties

Abstract: Background: The aim of this study was to evaluate the microarchitecture, composition and mechanical properties of cortical bone of rats with type I diabetes mellitus (TIDM) and submitted to insulin therapy (IT). Methods: Thirty rats were divided into three groups (n=10): non-diabetic, diabetic and diabetic+insulin. TIDM was induced by intravenous injection of streptozotocin. In diabetic+insulin group, 4IU insulin was administered twice per day (1IU at 7am and 3IU at 7pm). The animals were euthanized five w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Insulin therapy has been shown to reduce the deleterious effects of T1DM on rodent bone tissue. 45 The use of cinaciguat, a nitric oxide-independent activator of oxidized guanylate cyclase, reduced the oxidative stress induced by hyperglycemia and restored the osteoblast differentiation capacity of MSCs derived from mice with T1DM. 12 Clinically, it is possible to speculate that controlling glucose levels in patients with T1DM may help to reverse the bone damage induced by this metabolic disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin therapy has been shown to reduce the deleterious effects of T1DM on rodent bone tissue. 45 The use of cinaciguat, a nitric oxide-independent activator of oxidized guanylate cyclase, reduced the oxidative stress induced by hyperglycemia and restored the osteoblast differentiation capacity of MSCs derived from mice with T1DM. 12 Clinically, it is possible to speculate that controlling glucose levels in patients with T1DM may help to reverse the bone damage induced by this metabolic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the recovery of the normoglycemic environment partially restored the ability of MSCs derived from animals with T1DM to differentiate into osteoblasts. Insulin therapy has been shown to reduce the deleterious effects of T1DM on rodent bone tissue 45 . The use of cinaciguat, a nitric oxide‐independent activator of oxidized guanylate cyclase, reduced the oxidative stress induced by hyperglycemia and restored the osteoblast differentiation capacity of MSCs derived from mice with T1DM 12 .…”
Section: Discussionmentioning
confidence: 99%
“…This could be because our study was conducted on a pediatric patient group who were diagnosed for the first time and whose treatment has not yet started. In another study (22), it has been found that T1DM affects cortical thickness, fractal size, and bone microhardness, as well as microstructure and composition, and that insulin therapy reduces the effect Iran J Pediatr. 2024; 34(3): e142061.…”
Section: Gonial Index (Gi)mentioning
confidence: 97%